(untitled) (Issues in Social and Environmental Accounting (ISEA), 2015)
This paper examines the impact of corporate governance mechanisms on intellectual capital efficiency (ICE) of Nigerian Banks. The data for the study were generated from the audited financial statements of the sample banks for the period of 11 year (2003 - 2013). The study adopted Value Added Intellectual Co-Efficient (VAIC) methodology which includes three ICE components: human capital efficiency, structural capital efficiency and capital employed effi ciency. Corporate governance mechanisms considered in this study are Boards Composition, Managerial Rewards, and Ownership Structure. The study controls for the return on equity and leverage of banks. The regression results show that the corporate governance attributes consid ered in this study are good indicators of (ICE) because their impact are positively and signifi cantly at less than 1% with R-square of 58% and adj R-square of 55%. Also the two control variables are significantly related with intellectual capital efficiency. This implies that corpo rate governance have significant impact on ICE of firms in the Nigerian banking industry. Therefore, the study recommends that board should acquire political skills which are necessary to effective governance. In order to improve ICE, board should make it as their responsibility to develop and sustain healthy relationships and maintain open, two-way communication with all constituencies of staff in order to incite their IC towards organization’s success.